Shape Memory Alloys 2017 - Takuo Sakon (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Shape memory alloys (SMAs) have special property of the shape memory effect. After thermal treatment above the martensitic transition temperature, the alloys come back to the original shape when the alloys heat again after having cooled it to the temperature that is lower than the martensitic transition temperature. By means of this property, many industrial parts and systems were produced. This Special Issue "Shape Memory Alloys 2017" is constructed articles reporting new and progressive research results, as well as reviews of particular classes of fundamental physics of the materials and their applications of SMAs. Through its 17 efficient articles, the reader will approach to researches related to SMAs with their peculiar magnetic, thermo-mechanical properties, superelasticity, plastic deformation and compression under pressure. These physical properties introduce a large number of applications as faster SMA actuators, application of medical devices, industrial joining parts, volts, and magnetic/mechanical/thermal sensors. These articles are intended scientific researchers, professional engineers, students to obtain a better understanding in this field lately.